Hubungan Filsafat Ilmu Dengan Ilmu Pengetahuan dan Teknologi - Annastasya, Dara; Azzahra, Revadina Nazwa; Liyanandika, Yasha Agita; Monika, Elma; Astuti, Tania Dwi; Azahra, Aulia; N, Nurjanah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In general, the mother of all science is philosophy. Philosophy itself has developed greatly along with science and technology. Nowadays, many complex problems arise as technology develops and the emergence of these problems can change the mindset of today's society. Therefore, as an intermediary so that science and technology can be controlled, philosophy is used as the cornerstone of a science which indeed has a big role in the world of knowledge.